EFEKTIVITAS PELAKSANAAN PERATURAN WALIKOTA DENPASAR NOMOR 36 TAHUN 2018 TENTANG PENGURANGAN KANTONG PLASTIK DI PASAR KOTA DENPASAR - A.A Diah Sindy Vithaloka; I Wayan Eka Artajaya (Jurnal Hukum Mahasiswa, 2021)
The enactment of Mayor Regulation Number 36 of 2018 concerning Reduction of Plastic Bags has not made the public and business actors aware of the importance of reducing plastic bags because there are still people who do not bring alternative bags, on the other hand, business actors still provide plastic bags when transacting in the market, especially in Denpasar City. The method in this study uses a method with an empirical type of research. The conclusion of this study is that the effectiveness of the implementation of the Mayor's Regulation Number 36 of 2018 concerning Reduction of Plastic Bags in several Markets in the Denpasar City area is still not effective based on interviews with resource persons, which lies in community factors. Every member of the community or group has more or less legal awareness. In Denpasar Mayor Regulation Number 36 of 2018 concerning Reduction of Plastic Bags, people seem indifferent to the rule so that the level of community compliance is still minimal, many consumers complain about the rule. The factors that cause the availability of plastic bags in several markets in the Denpasar City area are inhibiting factors and supporting factors in the implementation of Denpasar Mayor Regulation Number 36 of 2018 concerning Reduction of Plastic Bags. The inhibiting factors are: Insufficient budget funds, Lack of Community Participation, Consumers complain a lot, Consumers cancel shopping, Lack of consumer interest to shop at the store, reduce store income while supporting factors, namely: Conducted socialization